2013
DOI: 10.1186/1477-7827-11-46
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of candidate molecules in the human fallopian tube and chorionic villi of tubal pregnancy exposed to levonorgestrel emergency contraception

Abstract: BackgroundCases of ectopic pregnancy (EP) following levonorgestrel (LNG) emergency contraception (EC) failure were reported, however, the effects of LNG on tubal microenvironment or chorionic villi in EP have not yet been documented.MethodsFifty-five women with tubal pregnancy were divided into two groups according to whether LNG-EC was administrated during the cycle of conception. The serum concentrations of beta-hCG, E2 and P were measured. The mRNA and protein expressions of estrogen and progesterone recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…). In addition, there were no differences in the patient’s serum progesterone concentrations immediately before the surgery for either the first or the second ectopic pregnancies as well as the previous report (Table ). The absence of tubal decidualization due to the decreased effect of progesterone might be one of the causes for the failure of the emergency contraception …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…). In addition, there were no differences in the patient’s serum progesterone concentrations immediately before the surgery for either the first or the second ectopic pregnancies as well as the previous report (Table ). The absence of tubal decidualization due to the decreased effect of progesterone might be one of the causes for the failure of the emergency contraception …”
Section: Discussionsupporting
confidence: 71%
“…Luteal progesterone level may have been disordered after delivery . Levonorgestrel does not have an effect on expression of PR and the concentration of progesterone . Fortunately, we could compare the ectopic pregnancies: the first pregnancy was affected by LNG‐EC use and the second was not affected by the previous LNG‐EC use.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, exposure to LNG also does not alter the expression of candidate molecules, such as oestrogen or P4 receptors, leukaemia inhibitory factor, vascular endothelial growth factor, inducible nitric oxide synthase and endocannabinoid receptor 1, which are potential regulators of the pathophysiological changes in tubal pregnancy in the fallopian tube and chorionic villi. 19 There is no reliable information regarding the effects of LNG effects on ciliary activity.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study on the candidate molecules involved in embryo development, we found no differences in the expression levels of these molecules in the chorionic villi in women with tubal EP exposed to LNG‐EC versus those with general tubal EP. Thus, we concluded that the etiological features but not pathophysiological or clinical features of specific tubal EP following LNG‐EC failure differed from those of general EP …”
Section: Discussionmentioning
confidence: 83%
“…Thus, we concluded that the etiological features but not pathophysiological or clinical features of specific tubal EP following LNG-EC failure differed from those of general EP. 44 The present study is the first to evaluate whether TP following LNG-EC failure was associated with fallopian tube inflammation using a combination of four objective measurements, involving serum CT IgG tests, laparoscopic examination, histopathological analysis, and Masson's staining. However, this study had some limitations.…”
Section: Discussionmentioning
confidence: 99%